New erythropoietic agents - Rokicka, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2004)
Cancer-related anemia is a serious complication that influences the quality of life and the treatment outcome of cancer patients. The search for improved methods of treatment of cancer-related anemia that may replace currently used methods such as red blood cell transfusions and erythropoietin (Epo) treatment is still in progress. Epo treatment of cancer-related anemia is very effective but the drug must be injected subcutaneously a few times a week. This article describes two new erythropoietin (Epo) modified derivatives, darbepoetin and CERA. They are characterized by novel pharmacological properties that make it possible to administer them less frequently in comparison to recombinant human Epo (rHuEpo) with the same therapeutic efficacy. Darbepoetin contains more sialic acid bound to protein molecule and this prolongs its circulating half-life. CERA hinges on the chemical modification of the protein part of Epo molecule and this enhances and sustains erythropoietic activity due to both an extended serum half-life and continuous interaction with Epo receptor. Thus the novel Epo stimulating agents can be administered less frequently. They are well tolerated without any significant adverse events. Clinical trials confirm their comparable efficacy to rHuEpo. These agents offer hope for better comfort of anemia treatment and better patients compliance.